Sistem Informasi Pemilihan Asisten Laboratorium dengan Metode Weighted Product dan Weighted Sum Model - Nur Hayati; Sri Rahayu; Tri Ichsan Saputra (Universitas Indraprasta PGRI Jakarta, 2021)
The process of selecting assistants at a faculty is generally based on requirements such as GPA, year of class, even some are accepted subjectively because of the direct assessment of a lecturer who is also the head of the laboratory. This form of election isn’t problematic as long as the student is indeed worthy of being an assistant. However, the documentation of such an admissions system is often not traceable. Therefore, an application for the assistant selection process is indispensable to make the process more documented and objective. Based on the conditions for accepting assistants that have previously been implemented, the Weighted Product decision support system method can be used in the weighting process because it is more specific to the value weights in each criterion and the Weighted Sum Model can be used for the ranking process so that the decision results can be precise, fast and objective. The results obtained were 100% test from the interface side and then the results of the study were in the form of a website-based information system for selecting laboratory assistants based on the criteria for GPA, practical course scores, specificity course scores and question scores.